Stromal vascular fraction injection to treat intractable radiation-induced rectovaginal fistula - Kim, Mijung; Lew, Dae Hyun; Roh, Tai Suk; Song, Seung Yong (Archives of plastic surgery, 2021)
Rectovaginal fistula, which can arise after an injury to the vaginal canal or rectum, is a troublesome obstacle for patients’ everyday life. In most cases, it can be covered with a local flap, but previous radiation therapy increases the recurrence rate, making it especially difficult to cure. As the application of stromal vascular fraction (SVF) obtained from enzymatically digested autologous adipose tissue has become increasingly common, several reports have advocated its effectiveness for the treatment of refractory wounds. In light of the angiogenic, regenerative characteristics of SVF, it was incorporated as a treatment option in two cases of rectovaginal fistula discussed here. As described in this report, irradiated rectovaginal fistulas in rectal cancer patients were successfully treated with SVF injection, and we suggest SVF as a feasible treatment option for cases of rectovaginal fistula that would otherwise be very difficult to cure.